The environmental situation and the environmental movement in Kazakhstan - Alimbaev, Т.; Utebaeva, А.; Akhmetzhanova, N.; Asankanov, A. (KSU Publ., 2017)
The article analyzes the ecological movement in Kazakhstan in 80–90’s of the XXth century. On the basis of the study of ecological associations’ Charters there were identified the main directions of this movement. It is a protection of the natural environment, the ecological consequences of unreasoned construction projects, long-term practice of placement and exploitation of large industrial enterprises, regardless of their impact on the natural conditions and human health, the mass movement for the closure of military sites. In the development of the ecological movement were shown two trends in Kazakhstan in the 70–90’s. The first trend has evolved under the influence of public-political and economical structures that sought to attract the masses to the solution of ecological issues, determined by the state. For this purpose there were assigned specific legal rules in the state-legal mechanism which ensure the participation of every person in the solution of nature conservation goals. The second trend in the development of the ecological movement is associated with the part of society that is more aware of the nature and risk of further deterioration of the ecological situation, acted with more radical demands and criticism of state policy. This part of the movement was of autonomous and independent nature from the state and political structures and has appeared in Kazakhstan after events of December 1986. However, the ecological movement in the 80’s and 90’s did not change the character and character of the relationship between society and nature.
Қазақстандағы экологиялық жағдай жəне табиғатты қорғау қозғалыстары
Экологическая ситуация и природоохранное движение в Казахстане
Keywords: natural resources; the ecological crisis; the ecological movement in Kazakhstan; the main trends and stages of environmental ecological movement; industrial enterprise; military polygons; people's health; ecology and politics